Penerapan Manajemen Krisis Oleh Humas PTPN XIII Dalam Membangun Citra Positif Perusahaan - Marlianto, Marlianto; Dewi, Sulih Indra; Rinata, Asfira Rachmat (Universitas Brawijaya, 2023)
This study aims to find out and understand how PTPN XIII public relations in the application of crisis management to build a positive company image and to find out the constraints of PTPN XIII public relations in the application of crisis management to build a positive company image. Using qualitative research methods with data collection techniques with interviews, observations, and documentation. The focus of this research is: The application of crisis management by PR PTPTN xiii in building a positive image of the company by using the following indicators: knowing the problem (fact finding), planning (planning and programming), taking action and communicating (action and communicating), processing crises , deepening of data and facts, making issue boundaries, appointing spoke persons, factors that become obstacles to the implementation of crisis management. The result of this research is the implementation of PTPN XIII's public relations crisis management in building a positive company image by collecting data, facts and information. By understanding the various problems in the field, public relations directly convey these problems to the head office. Taking action and communication to make the public understand and understand the company's policies, then while building a positive image of the company, public relations also carries out on-the-spot activities, such as community activities, social assistance and public facilities.